Sexualities in anthropology : a reader - Lyons, Andrew P. [ (Andrew Paul] , 1944-; Lyons, Harriet D. , 1943-; Weston, Kath , 1958- (Blackwell Anthologies in Social and Cultural Anthropology, 2011)
"Shedding important new light on a subject as old as humanity itself, Sexualities in Anthropology: A Reader presents a comprehensive collection of historical and current readings in the social anthropology of sexuality. Succinct and revealing excerpts from key figures in the history of anthropology about sexualities, morality, and the family are featured. The most recent literature on both heterosexualities and same-sex sexualities is also included, as well as material on past and present controversies, including Derek Freeman's famous attack on Margaret Mead's writings on sexual freedom in Samoa; the notion of "primitive" promiscuity in the 19th and early 20th centuries; concerns for the practice of clitoridectomy and other forms of "genital cutting;" the discussion of homosexualities in different cultures; and the meaning of love. Thought-provoking and always fascinating, Sexualities in Anthropology: A Reader offers keen insights into the diversity of human social beliefs, practices, and interactions relating to human sexual behavior around the world"